(untitled) (Al-Academy, 2024)
In advertising, the designer practices Westernization by manipulating ideas and treatments. He avoids adherence to familiar reality and creates unique works of art that are alien to the prevailing social and environmental pattern. This is evident in the design of advertisements in creative ways that go beyond the traditional framework, which is linked to intellectual worlds of an imaginative and inspiring nature. The theoretical framework deals with the formation of print advertising and all types of graphic design schools, as well as the research procedures represented by the research population, the sample, the research tool, sample analysis, and the results and conclusions reached by the researcher, including. 1- The researcher concluded that the designer relied on writing the title (text) in large, clear letters to arouse interest. 2- The use of pictures and drawings gave an aesthetic, expressive and illustrative function